2014
DOI: 10.1080/09168451.2014.943689
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response machineries of Bacillus subtilis conducive to plant growth promotion

Abstract: Bacillus subtilis collectively inhabits the rhizosphere, where it contributes to the promotion of plant growth, although it does not have a direct symbiotic relationship to plants as observed in the case of rhizobia between leguminous plants. As rhizobia sense the flavonoids released from their host roots through the NodD transcriptional factor, which triggers transcription of the nod genes involved in the symbiotic processes, we supposed that B. subtilis utilizes certain flavonoids as signaling molecules to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
(124 reference statements)
0
12
0
1
Order By: Relevance
“…Gram positive Bacillus spp. are a major component of rhizosphere microbial communities [52, 53], and are frequently categorised as Plant Growth Promoting Rhizobacteria (PRPR) [54, 55]; B . subtilis has also been shown effective in controlling Meloidogyne species [56].…”
Section: Discussionmentioning
confidence: 99%
“…Gram positive Bacillus spp. are a major component of rhizosphere microbial communities [52, 53], and are frequently categorised as Plant Growth Promoting Rhizobacteria (PRPR) [54, 55]; B . subtilis has also been shown effective in controlling Meloidogyne species [56].…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis species have often been isolated from the rhizosphere of various terrestrial plants; many of them have been shown to be plant growth-promoting rhizobacteria whose association with the plant roots enhances the adaptive potential of plants and increases their growth (1). Interestingly, B. subtilis is also a saprophytic bacterium that secretes various degrading enzymes, including those able to hydrolyze the polysaccharides that constitute the plant cell wall, although it does not prey on the living plant cells (2).…”
mentioning
confidence: 99%
“…Table 1: Differentially-expressed proteins identified in the proteomic screen. Comparison between 168 cytosolic crude extracts from 168 Bacillus subtilis strains grown in LB medium with or without stress (ZnO nanoparticles or ZnSO 4 salt stress) ( Figure 2) (1) Spot number pointed out in Figure 2, (2) accession number from UniProKB, (3) protein function described by UniProtKB, (4) molecular weight, (5) pI, (6) number of peptides identified by mass spectrometry (7) percentage of coverage, (8) and (10) average quantification of the spot using Delta2D software from three independent 2-DE gels in the control, (9) and (11) standard deviation of the considering spot growth condition and (9) ratio of the average quantification determined by the Delta 2D analysis: stressed/not stressed.…”
Section: Acknowledgmentsmentioning
confidence: 99%